2017
DOI: 10.2527/jas2017.1752
|View full text |Cite
|
Sign up to set email alerts
|

Genomic study and Medical Subject Headings enrichment analysis of early pregnancy rate and antral follicle numbers in Nelore heifers1,2

Abstract: Zebu animals () are known to take longer to reach puberty compared with taurine animals (), limiting the supply of animals for harvest or breeding and impacting profitability. Genomic information can be a helpful tool to better understand complex traits and improve genetic gains. In this study, we performed a genomewide association study (GWAS) to identify genetic variants associated with reproductive traits in Nelore beef cattle. Heifer pregnancy (HP) was recorded for 1,267 genotyped animals distributed in 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 131 publications
3
18
1
Order By: Relevance
“…Júnior et al [54] reported higher heritability estimates for AFP (0.49 ± 0.09) in Nellore cattle compared to our findings. Moderate to high positive genetic correlations between AMH and AFP were reported to range from 0.56 to 0.68 in Nellore cattle and 0.73 to 0.90 in Holstein animals [52,55].…”
Section: Discussioncontrasting
confidence: 70%
“…Júnior et al [54] reported higher heritability estimates for AFP (0.49 ± 0.09) in Nellore cattle compared to our findings. Moderate to high positive genetic correlations between AMH and AFP were reported to range from 0.56 to 0.68 in Nellore cattle and 0.73 to 0.90 in Holstein animals [52,55].…”
Section: Discussioncontrasting
confidence: 70%
“…For instance, prevalence of infertility may reach 16% 2 and 15% 3 in humans and beef female calves, respectively. Similar to what has been observed in humans 4 , the genetic architecture of fertility in beef heifers is very complex 5,6,7,8,9,10,11,12 . In line with this complexity, female reproductive traits have low heritability.…”
Section: Introductionsupporting
confidence: 68%
“…The examination of the genetic components of fertility in beef heifers have yielded several genes potentially associated with fertility traits 5,6,7,8,9,10,11,12 , but the effect of these markers are minimal, and there is no clear redundancy in genetic markers identified across breeds. Beyond the genomic profiling, the analysis of multiple layers of an individual’s molecular blueprint is likely key for understanding the underlying biology of complex traits 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Dias and others identified three haplotypes significantly associated with heifer pregnancy, which contained the genes fatty acid binding protein 4 (FABP4) and protein phosphatase 3 catalytic subunit alpha (PPP3CA) [85]. Focusing on chromosomic regions, two studies identified chromosome regions that explained as much as 8.91% [86] and 12.73% [87] of the variance in sexual precocity to become pregnant by 16 months of age and heifer pregnancy, respectively. Of note, both studies identified windows on chromosomes 5, 14, and 18, with a potential overlap on chromosome 14 [86,87].…”
Section: Dna Polymorphismsmentioning
confidence: 99%
“…Focusing on chromosomic regions, two studies identified chromosome regions that explained as much as 8.91% [86] and 12.73% [87] of the variance in sexual precocity to become pregnant by 16 months of age and heifer pregnancy, respectively. Of note, both studies identified windows on chromosomes 5, 14, and 18, with a potential overlap on chromosome 14 [86,87]. Takada and others focused on haplotypes encompassing 125 candidate genes and identified nine haplotypes with significant association with early pregnancy.…”
Section: Dna Polymorphismsmentioning
confidence: 99%